Studi Kasus Manajemen Sekolah Inklusi SDN Manahan Surakarta - Hafizh, Ahmad; Widyastono, Herry; Sunardi, Sunardi (Jurnal Pendidikan Kebutuhan Khusus, 2020)
Inclusive education is one form of special education in Indonesia to provide opportunities for children with special needs to get an education. But the reality faced by inclusive schools in management and implementation has not been satisfactory. Many things are not in accordance with predetermined standards. In this study using a qualitative approach with a case study design. The research technique was carried out by non-participant observation, in-depth interviews and documentation studies. The results obtained show that the management of inclusive schools is still unsatisfactory such as the lack of facilities and accessibility of children with special needs, special educators, special assistant teachers. This will certainly affect the quality of education, learning processes, and evaluations carried out so that certain stages also have an impact on the outputs and outcomes of students with special needs